Individually-tailored multifactorial intervention to reduce falls in the Malaysian Falls Assessment and Intervention Trial (MyFAIT): A randomized controlled trial - Tan, P.; Khoo, E.; Chinna, K.; Saedon, N.; Zakaria, M.; Zahedi, A.; Ramli, N.; Khalidin, N.; Mazlan, M.; Chee, K.; Abidin, I.; Nalathamby, N.; et al. (Public Library of Science, 2018)
Objective: To determine the effectiveness of an individually-tailored multifactorial intervention in reducing falls among at risk older adult fallers in a multi-ethnic, middle-income nation in South-East Asia. Design: Pragmatic, randomized-controlled trial. Setting: Emergency room, medical outpatient and primary care clinic in a teaching hospital in Kuala Lumpur, Malaysia. Participants: Individuals aged 65 years and above with two or more falls or one injurious fall in the past 12 months. Intervention: Individually-tailored interventions, included a modified Otago exercise programme, HOMEFAST home hazards modification, visual intervention, cardiovascular intervention, medication review and falls education, was compared against a control group involving conventional treatment. Primary and secondary outcome measures: The primary outcome was any fall recurrence at 12-month follow-up. Secondary outcomes were rate of fall and time to first fall. Results: Two hundred and sixty-eight participants (mean age 75.3 ±7.2 SD years, 67% women) were randomized to multifactorial intervention (n = 134) or convention treatment (n = 134). All participants in the intervention group received medication review and falls education, 92 (68%) were prescribed Otago exercises, 86 (64%) visual intervention, 64 (47%) home hazards modification and 51 (38%) cardiovascular intervention. Fall recurrence did not differ between intervention and control groups at 12-months [Risk Ratio, RR = 1.037 (95% CI 0.613–1.753)]. Rate of fall [RR = 1.155 (95% CI 0.846–1.576], time to first fall [Hazard Ratio, HR = 0.948 (95% CI 0.782–1.522)] and mortality rate [RR = 0.896 (95% CI 0.335–2.400)] did not differ between groups. Conclusion: Individually-tailored multifactorial intervention was ineffective as a strategy to reduce falls. Future research efforts are now required to develop culturally-appropriate and affordable methods of addressing this increasingly prominent public health issue in middle-income nations.